IUPHAR review: From gut to brain: The role of gut dysbiosis, bacterial amyloids, and metabolic disease in Alzheimer’s disease - Saadet Inan; R. Paul Wilson; Çagla Tükel (Pharmacological Research)
Gut microbial dysbiosis, or altered gut microbial communities, in Alzheimer’s Disease suggests a pathogenic role for gut inflammation and microbial products in shaping a neuroinflammatory environment. Similarly, metabolic diseases, such as obesity and diabetes, are also associated with an increased risk of Alzheimer’s Disease. As the metabolic landscape shifts during gut inflammation, and gut inflammation in turn impacts metabolic processes, we explore how these interconnected pathways may contribute to the progression of Alzheimer’s Disease. Additionally, we discuss the role of bacterial amyloids produced by gut microbes, which may exacerbate amyloid aggregation in the brain and contribute to neurodegenerative processes. Furthermore, we highlight potential therapeutic strategies aimed at reducing gut inflammation, improving metabolic health, and decreasing amyloid content as a means to mitigate Alzheimer’s Disease progression. These approaches, targeting the gut-brain-metabolic axis, could offer promising avenues for delaying or preventing cognitive decline in affected individuals.